Kolaborasi Pengembangan Destinasi Wisata Pedesaan di Kelurahan Buraen Kecamatan Amarasi Selatan Kabupaten Kupang - Nursalam Nursalam; Djaha Ajis S. Adang; Melkisedek N.B.C. Neolaka; William Djani; Alfred O.Ena Mau (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
Abstract Rural tourism is an alternative tourist destination because of its attractive potential, so that many rural areas are visited. Community service carried out by the community service team for the Master of Public Administration study program, Fisip Undana, aims to provide education to the community related to the development of rural tourism through collaboration. Based on the results of a situation analysis of the existence of collaboration in developing destinations in the Buraen sub-district, the problems encountered are; (a) still weak participatory planning in the development of tourist destinations; (b) Tourism destination infrastructure development policies have not been carried out systematically and continuously; (c) the pattern of collaboration is still limited to cooperation between governments, other sectors namely the private sector and the community have not been involved. The solution offered from partner problems is to carry out a community service activity through the form of education. The activities carried out are socializing and providing knowledge to the audience about; (a) the importance of participatory-based planning in the development of rural tourism destinations; (b) incremental policies in the development of rural tourism destinations; (c) collaborative development of rural tourism destinations. While the PkM program assessment method is through program evaluation and outcome evaluation. Based on the results of PkM activities, it is known that all participants understand the socialization material about; (a) participatory-based planning in the development of tourist destinations; (b) incremental policies in the development of tourist destinations; (c) collaborative development of rural tourism destinations. It is recommended that collaborative development of tourist destinations is not just an idea but should be implemented and also involve the community so that they can benefit from rural tourism activities. Keywords: 1. Rural Tourism; 2. Participatory Planning; 3. Incremental policy; 4. Collaboration Abstrak Pariwisata pedesaan merupakan salah satu alternatif destinasi wisata karena potensi daya tariknya, sehingga wilayah pedesaan banyak dikunjungi. Pengabdian kepada masyarakat yang dilakukan oleh tim PPM Prodi Magister Administrasi Publik Fisip Undana bertujuan memberikan Pendidikan kepada masyarakat berkaitan dengan pengembangan pariwisata pedesaan melalui kolaborasi antar berbagai pihak di kelurahan Buraen kecamatan Amarasi Selatan kabupaten Kupang. Berdasarkan hasil analisis situasi terhadap kolaborasi dalam pengembangan destinasi di kelurahan Buraen, masalah yang dihadapi adalah; (a) masih lemahnya perencanaan partisipatif dalam pengembangan destinasi wisata; (b) Kebijakan pengembangan infrastruktur destinasi wisata belum dilakukan secara sistimatis dan berkesinambungan; (c) pola kolaborasi masih terbatas pada kerjasama antar pemerintah, sektor lain yaitu swasta dan masyarakat belum dilibatkan. Solusi yang ditawarkan dari permasalahan mitra adalah dilakukan suatu kegiatan pengabdian masyarakat melalui bentuk Pendidikan. Bentuk kegiatan yang dilakukan adalah mensosialisasikan dan memberikan pengetahuan kepada audien tentang; (a) pentingnya perencanaan berbasis partisipatif dalam pengembangan destinasi wisata pedesaan; (b) kebijakan inkremental dalam pengembangan destinasi wisata pedesaan; (c) kolaborasi pengembangan destinasi wisata pedesaan. Sedangkan metode penilain program PKM adalah melalui evaluasi program dan evaluasi hasil. Hasil sosialisasi adalah seluruh peserta memahami tentang; (a) perencanaan berbasis partisipatif dalam pengembangan destinasi wisata; (b) kebijakan inkremental dalam pengembangan destinasi wisata; (c) kolaborasi pengembangan destinasi wisata pedesaan. Direkomendasikan agar kolaborasi pengembangan destinasi wisata tidak hanya merupakan suatu ide belaka tetapi seharusnya diimplementasikan dan juga melibatkan masyarakat agar mereka mendapat manfaat dalam kegiatan pariwisata pedesaan. Kata Kunci: 1.Pariwisata pedesaan; 2. Perencanaan Partisipatif; 3. Kebijakan Inkremental; 4. Kolaborasi